The holographic anthropic multiverse : formalizing the complex geometry of reality - Amoroso, Richard L. (K & E series on knots and everything, 2009)
Every hundred years or so, a unique groundbreaking Copernican class volume arises unexpectedly. From ashes long thought cold of Einstein's static universe model, for the first time technically viable alternative interpretations to all pillars of Big Bang cosmology are presented in the context of a profound new "continuous-state" cosmological paradigm able to elucidate many contemporary problems plaguing the standard model of particle physics. The cosmology provides an alternative derivation of the string/brane tension formalism derived from large-scale additional dimensions that leads to a putative unique background-independent string vacuum without requiring the Higgs mechanism or SUSY superpartners. Breakthroughs presented, arising from the broad spectrum of explanatory power, include an empirical protocol for violation of the quantum uncertainty principle that provides a viable model for the implementation of universal bulk quantum computing. Other developments naturally arising from utility of the new regime include a design for constructing de Broglie-type matter-wave projectile defense shields with far-reaching consequences